Financial Stability in Emerging Economies in the Near Future - Carvalho, Fernando Cardim de (Brazilian Keynesian Review, 2016)
Financial Stability in Emerging Economies in the Near Future Emerging economies have gone through a reversal of fate lately. In the aftermath of the financial crisis of 2007/8, the group was considered to be the next frontier of expansion of world capitalism. Nowadays, most of the countries in the group are mired in difficulties and are seen as a threat to international economic stability rather than an engine of growth. In this comment, we explore some key fragilities that are recognized in emerging economies, particularly those related to the accumulation of private debt. The perspectives for the near future are proposed to illustrate Keynes’s concept of true uncertainty and encourage the search for liquidity by wealth-holders worldwide.